Urgency of Culture-Based Education Policy at State Junior High School 7 Yogyakarta - Riyadi, Benyamin Ananda (Fakultas Ilmu Pendidikan, 2025)
This research aims to identify and describe: 1) Urgency of culture-based education at State Junior Highschool 7 Yogyakarta; 2) The implementation of culture-based education at State Junior Highschool 7 Yogyakarta; 3) The supporting and inhibiting factors of the implementation of culture based education at State Junior Highschool 7 Yogyakarta. This research is qualitative with based practice approach. The subject included the vice-principal, teacher, and student. Data collection technique of this research was using observation, interview, and documentation studies. Data analysis is conducted through Miles and Huberman technique and technique triangulation for data validation. The results of this research are: 1) Culture-based education at State Junior Highschool 7 Yogyakarta is conducted through teaching and learning process and various cultural activities; 2) Implementation of culture-based education at State Junior Highschool 7 Yogyakarta from the aspects of a) communication is conducted through socialization and discussion between school, student, and parents; b) resources, included human resource and limited facilities for supporting the implementation; c) bureaucracy structure involving committee, head principal, vice-principal, teacher, and student; d) disposition of implementer at school who have a dedication for culture-based education. 2) The support factor is the disposition of the implementers, while the inhibited factor is the limited resources.